Math, asked by queenpaarul, 9 months ago

i) On simplifying
7+ [12 - {8 + 3 - (9 of 6 - 13 x 4 + 1)}],



Answers

Answered by aradhyaaishwarya20
0

Answer:

7+ [12- {8+3-(9×6-13×4+1)}]

=7+[12-{8+3-(54-52+1)}]

=7+[12-{8+3- (2+1)}]

=7+[12-{8+3-3}]

=7+[12-{11-3}]

=7+[12-8]

=7+ 4

=11

Follow BODMAS

means first solve bracket

then of (×)

then division

then multiplication

then addition

then subtraction

Answered by prabhdayal5639
0

7+[12-{8+3-(9×6-13×4+1)}]

7+[12-{8+3-(54-52+1)}]

7+[12-{8+3-(3)}]

7+[12-{11-3}]

7+[12-8]

7+4

11

the answer is 11

hope it helps u

plz mark it as brainliest answer

Similar questions